Between constitution and interpretation: On narrating Identities - Annette Hilt (Cusanus Hochschule für Gesellschaftsgestaltung, Institute für Ökonomie und für Philosophie, 2020)
Identity is rooted in a shared reality, where we also experience limits of this (social) reality. The shared reality is right the reality where our specific experiences gain their typical orientating strength. The heuristic point of an approach starting from limits of shared experiences (i.e. "finite provinces of meaning" that define common grounds and rules of our understanding) is the insight in those structures of our capacity to deal with ambiguous and even failing understanding. This topic will be explored through a dialogue between Alfred Schutz's phenomenological categories of constituting and understanding meaning and Imre Kertész' literary expression of a life lived at the edge of the social sphere and a mutually recognized identity.
Keywords: 300; Phenomenology of the social world; Alfred Schutz; Thomas Luckmann; Hermeneutics; Narrative Identity; Concepts of Self and Identity